PENYERAPAN TENAGA KERJA LOKAL PADA SEKTOR MIGAS KAWASAN JAMBARAN TIUNG BIRU KABUPATEN BOJONEGORO - Widiana, Andria; Moehadi, Moehadi; Taufiqqurachman, Fahrizal (Universitas Negeri Yogyakarta, 2022)
The natural oil and gas industry plays a role in pumping up Bojonegoro's economic growth chart so that people can find it easier to get work. This study aims to find out how many local residents are absorbed into the workforce in the Jambaran Tiung Biru area. Respondents of this study are workers in Jambaran Tiung Biru. The analysis technique used is SWOT analysis. The results of the study show that the Jambaran Tiung Biru area is in quadrant I, so the strategy that can be carried out is an aggressive strategy, where this aggressive strategy requires companies and workforce to focus on: (1) ease of getting jobs to reduce unemployment for local residents (2) ) the promised salary is quite large if you work according to your expertise (3) get a job according to your expertise if there is training (4) good performance will easily extend the contractKeywords: Oil and Gas, Labor, Absorption